Cancer Stem Cells: A Minor Cancer Subpopulation that Redefines Global Cancer Features - Enderling, Heiko; Hlatky, Lynn; Hahnfeldt, Philip (Frontiers in Oncology, 2013)
In recent years cancer stem cells (CSCs) have been hypothesized to comprise only a minor subpopulation in solid tumors that drives tumor initiation, development and metastasis; the so-called “cancer stem cell hypothesis”. While a seemingly trivial statement about numbers, much is put at stake. If true, the conclusions of many studies of cancer cell populations could be challenged, as the bulk assay methods upon which they depend have, by and large, taken for granted the notion that a ‘typical’ cell of the population possesses the attributes of a cell capable of perpetuating the cancer, i.e., a CSC. In support of the CSC hypothesis, populations enriched for so-called ‘tumor-initiating’ cells have demonstrated a corresponding increase in tumorigenicity as measured by dilution assay, although estimates have varied widely as to what the fractional contribution of tumor-initiating cells is in any given population. Some have taken this variability to suggest the CSC fraction may be nearly 100% after all, countering the CSC hypothesis, and that there are simply assay-dependent error rates in our ability to ‘reconfirm’ CSC status at the cell level. To explore this controversy more quantitatively, we developed a simple theoretical model of cancer stem cell-driven tumor growth dynamics. Assuming CSC and non-stem cancer cell subpopulations coexist to some degree, we evaluated the impact of an environmentally-dependent cancer stem cell symmetric division probability and a non-stem cancer cell proliferation capacity on tumor progression and morphology. Our model predicts, as expected, that the frequency of CSC divisions that are symmetric highly influences the frequency of CSCs in the population, but goes on to predict the two frequencies can be widely divergent, and that spatial constraints will tend to increase the CSC fraction over time.